Fiction in the age of risk. Issue 3 (16th April 2017) - Hughes-d'Aeth, Tony; Nabizadeh, Golnar
ABSTRACT: When Ulrich Beck theorised a 'Risk Society' ( Risikogesellschaft ) in 1986, the threat of global annihilation through nuclear war remained uppermost in the minds of his readership. If we skip forward three decades to the contemporary moment, the question we ask in this special issue is whether the sensation of risk has mutated or evolved in the intervening period and whether fiction exhibits evidence of such a change. While the immediate risk of the Cold War's 'mutually assured destruction' through World War Three seems to have ebbed, the paradox is that the social goal of safety and security seems not to have drawn any closer. Global financial collapse, Islamic terrorism, human-authored climate change, epidemic disease outbreaks, refugee crises and the chronic erosion of the welfare state now preoccupy those in the developed world and provide the horizons for our anxieties. These concerns run through contemporary fiction and are analysed in the essays in this special issue.